Accelerated calcite precipitation (ACP) method for recycled concrete aggregate (RCA). (30th October 2016) - Nam, Boo Hyun; An, Jinwoo; Youn, Heejung
Highlights: Evaluate short- and long-term geochemical reaction of RCA regarding calcite precipitation. Develop Accelerated Calcite Precipitation (ACP) method for RCA. Use the short-term ACP to evaluate the effect of rock type and fines. Use the long-term ACP to determine the lifetime calcite precipitation. Utilize petrographic analysis tools to check existing chemical conditions of RCA. Abstract: Recycled concrete aggregate (RCA) is often used as a replacement of virgin aggregate in embankments, roadbed, asphalt and concrete pavements. The use of RCA in drainage systems as pipe backfill materials has not received a large attention due to clogging potential. Calcite precipitation is one of major causes of permittivity reduction in filter fabrics. The calcite formation is a long-term process; thus, a means to evaluate the potential of calcite precipitation in an accelerated manner is necessary. In this study, an accelerated calcite precipitation (ACP) procedure of RCA was developed, and its performance was evaluated. Two types of ACP methods were devised: short-term and long-term simulations. The long-term ACP procedure can be used to determine maximum lifetime calcite precipitation while the short-term ACP procedure can be used to evaluate the effect of test variables (e.g. aggregate type, fine content, etc.) on the calcite precipitation.